The handbook of law and society - Sarat, Austin; Ewick, Patricia (Wiley handbooks in criminology and criminal justice, 2015)
"Bringing a timely synthesis to the field, The Handbook of Law and Society presents a comprehensive overview of key research findings, theoretical developments, and methodological controversies in the field of law and society.